The gut microbiome of the neotropical beetle Veturius sp. (coleoptera: passalidae): structure, composition and geneticpotential for cellulose degradation - Vargas Asensio, Juan Gabriel (2020)
The global carbon cycle is responsible for maintaining the carbon dioxide and methane concentration in the atmosphere, influencing the weather and ocean acidification. Herbivores play an important role in the carbon cycle. However, the microorganisms that inhabit their guts are the ones responsible for the cellulose breakdown and consequent release of greenhouse gases such as CO2 and methane. Here we studied the gut microbiome of the Passalid beetle Veturius sp., from Braulio Carrillo National Park, Costa Rica. Veturius sp. only feed on decay wood and presents a subsocial behavior that may lead to the acquisition and sharing of microbial symbionts for efficient biomass and energy production. Family groups from different logs in the forest were sampled and the gut microbiome of larvae and adults as well as the woody gallery material (substrate) in which they resided was analyzed. The structure and composition of the communities was determined using amplicon sequencing of 16S rRNA genes. These results were then used in order to select the samples to perform metagenomic sequencing for further functional analysis and genome reconstruction. The results showed that adult, larvae and gallery material harbor significantly different communities, sharing less than 3% of total OTUs (total OTUs in the system= 11 712), with the gallery woody substrate having the higher diversity (3178 observed species) and richness (chao=6714). Firmicutes and Euryarchaeota were the dominant phyla in adults and larvae gut. The most abundant families of Firmicutes included Clostridiaceae, Lachnospiraceae and Ruminococcaceae, all known for its cellulose degradation capacity. A total of 766 partial genomes were reconstructed using the metagenomic sequences from adult, larvae and substrate; 101 of were classified as metagenome assembled genomes (MAG). Larvae and adults are enriched in microorganism with genomes having a myriad of glycosyl hydrolases, and other functions related to carbon metabolism; furthermore, methanogenesis markers were found in the larval partial genomes, suggesting that those performed the final steps of cellulose decomposition. Finally, the Veturius sp. metagenomes were compared with datasets from other cellulolytic systems, the results showed evidence of convergent evolution of functions between the larvae and cow rumen, suggesting that Veturius sp. and other beetle larvae are unexplored, yet important contributors to the carbon cycle and the biotic production of the greenhouse gas methane. The Passalid microbiome is important to the ecology and physiology of these beetles.